Change of dielectric properties of ceramics in lead magnesium niobate-lead titanate system with compressive stress - Rattikorn Yimnirun (2018)
Effects of compressive stress on the dielectric properties of PMN-PT ceramics were investigated. The ceramics with the formula (1 - x)Pb(Mg 1/3Nb2/3)O3-(x)PbTiO3 or (1 - x)PMN-(x)PT (x ≤ 0.1-0.5) were prepared by a conventional mixed-oxide method and then characterized with x-ray diffraction (XRD) and scanning electron microscopy. Dense perovskite-phase PMN-PT ceramics with uniform microstructure were successfully obtained. The dielectric properties under compressive stress were observed at stress up to 230 MPa using a home-built compressometer. The experimental results revealed that the superimposed compression stress significantly reduced both the dielectric constant and the dielectric loss tangent of 0.9PMN-0.1PT ceramic, while the changes were not as significant in the other PMN-PT ceramic compositions. In addition, the dielectric properties were considerably lowered after a stress cycle. Since change in the dielectric properties with applied stress was attributed to the competing influences of the intrinsic and the extrinsic contributions, the observations were mainly interpreted in terms of domain switching through non-180° domain walls, de-ageing, clamping of domain walls and the stress induced decrease in the switchable part of spontaneous polarization. © 2006 IOP Publishing Ltd.